The Implementation Of Visual Media In The Form Of Images In Indonesian Language Learning For Elementary Schools - Majdi, Muhammad; Hartati, Leni; Nahda, Maisah (The International Journal of Education Management and Sociology, 2024)
Visual media, such as images, plays a crucial role in Indonesian language learning at the early stages (Grades 1 and 2), particularly in the topic of "Hobbies That Become Achievements". Image media can clarify concepts that might be difficult for students to understand, especially in the context of hobbies that have the potential to become achievements. Given the importance of visual understanding in this learning process, it is essential to investigate the effectiveness of image media in enhancing student comprehension and to evaluate any limitations that may arise. This study employs a qualitative approach. Data was collected through direct observation, interviews with teachers, and analysis of student learning documentation before and after the use of image media. The analysis process involved identifying common patterns in students' interactions with image media and its impact on their understanding of the material and student engagement. The findings indicate that the use of image media significantly improves students' understanding of the material about hobbies. Students were able to identify and explain various hobbies that could become achievements more effectively compared to before using image media. Image media also enhances student engagement in the learning process, making it more enjoyable and interactive. However, a limitation was found: image media is restricted in conveying abstract and complex concepts. The proposed solution is that teachers should master the material and appropriate teaching methods to maximize the effectiveness of image media.